PROBLEMATIKA KEBAHASAAN DALAM PENGGUNAAN BAHASA INDONESIA KONTEMPORER - Suyitno, Nazma Hidayanti Putri (Universitas Peradaban, 2025)
This study examines various linguistic problems in the use of contemporary Indonesian, particularly in the digital age. Numerous language errors were identified across several media platforms such as social media, public spaces, and formal discourse. These errors include incorrect spelling, punctuation mistakes, improper word choice, ineffective sentence structures, inappropriate loanword usage, code-mixing and code-switching, as well as illogical or ambiguous expressions. Employing a descriptive qualitative approach, the study used reading, note-taking, and documentation techniques to collect data from written and spoken sources. The findings reveal that linguistic deviations occur frequently due to the public’s weak understanding of standard Indonesian language rules, compounded by the influence of popular culture and unregulated digital communication. Therefore, language education and increased linguistic literacy are essential to preserving the dignity of the Indonesian language. This research is expected to serve as a foundation for raising public awareness about the importance of proper language use in all aspects of life.